The Challenges of Service Delivery by Charities in Ghana: The Case of Rotary - Janet Serwah Gollo; J. Atsu Amegashie (CESifo GmbH, 2024)
We investigated the factors that negatively affect the service delivery capacity of charities in Ghana by using seven Rotary clubs as a case study. Primary data was collected via a survey of executives of the seven Rotary clubs. Our analysis revealed that the three main challenges that Rotary clubs face, in descending order of importance, were inadequate financial resources, unfavourable government policies, poor governance, and bad attitudes of the beneficiaries of Rotary clubs' charitable projects. The size of a club did not seem to have a positive effect on its service delivery capacity. We attributed this to a higher incidence of free-riding or apathy within bigger clubs. Indeed, we found that the lack of Rotarians' involvement in projects, scope creep of projects, and Rotarians' poor engagement with communities also had an adverse effect on service delivery.
Keywords: L30; L31; 330; charities; governance; Rotary; service delivery